Soybean molasses replacing cracked corn grain improves intake stability in feedlot lambs - Pereira-Junior, Sérgio Antonio Garcia; Arruda, Maria Carolina Gonçalves; Costa, Rayanne Viana; Castro Filho, Edivilson; Rodrigues, Julia Lisboa; Almeida, Marco Túlio Costa; van Cleef, Eric Haydt Castello Branco; Ezequiel, Jane Maria Bertocco (Acta Scientiarum. Animal Sciences, 2025)
In this study, we assessed the effects of replacing cracked corn grain with soybean molasses (SM) on the feed intake and ingestive behavior of 30 uncastrated lambs, Santa Inês × Dorper crossbreed, finished in feedlot. The treatments were 0 g kg-1 DM SM (CON), 150 g kg-1 DM SM (SM15), and 300 g kg-1 DM SM (SM30). Dry matter and nutrient intake were evaluated, in addition to ingestive behavior variables such as interactions with the feed bunker, stereotypes, chewing activities, and time spent in feed bunkers in a 24-h period at three different times during the feedlot period (beginning, middle, and end). The replacement of cracked corn grain with SM decreased the dry matter intake % BW (p < 0.05) and ether extract intake (p < 0.05) only at the final feedlot period. Additionally, it linearly decreased the cud chewing time p = 0.01) and increased the number of cuds (p = 0.02). The inclusion of SM allowed for a more stable feed intake during the feeding times (p < 0.05). Replacing cracked corn grain with SM in feedlot lamb diets offers a viable alternative without negatively affecting feed intake, even at levels of up to 300 g kg-1. This substitution improves the stability of feed intake.